Model Pengembangan Bahan Ajar Aqidah Akhlak (Studi Kasus Kelas Reguler dan Kelas Akselerasi MTs Negeri Ponorogo) - Asfahani Asfahani (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
Abstract Aqidah Akhlak is a very important and useful subject both in inculcate also form the moral of learners into a virtuous generation. In MTsN Ponorogo, the learning method and teaching materials of Aqidah Akhlak are different between regular class and acceleration class. Curriculum, syllabus of existing competency standard and basic competence in acceleration class not in accordance with the standard of content that has been determined from government or education curriculum applicable for learning only taken two years. In this study, researcher used a qualitative approach to the type of case study research. Data collection techniques with interview techniques, observations, and documentation that we do in MTsN Ponorogo. While data analysis techniques used are data reduction, data display, and conclusion. The results showed that, firstly; model development of teaching materials of Aqidah Akhlak in MTsN Ponorogo by using module “Aqidah Akhlak”. The module is compiled and developed by teachers by following the training, teaching materials development workshop, MGMP, make a summary and hand out the material of Aqidah Akhlak itself especially in acceleration class. Second; MTsN Ponorogo teachers are already creative with various methods and techniques of delivering teaching materials and hand out (module) material to students. With the support of facilities that are quite adequate because it is based on technology in the delivery of materials in the classroom, especially in the acceleration class in which students have above average intelligence so that it becomes its own demands for teachers. Keywords: Aqidah Akhlak, Teaching Materials, Development Models Teaching Materials.